Опрацювання власних імен у перекладних російсько-українських словниках - Самойлова, І. (Лексикографічний бюлетень, 2011)
The article deals with the problems of studying of personal names of people. Dictionaries where personal names are entered into the dictionary case, and dictionaries where personal names are taken out in separate section are considered. The special attention is given to L. H. Skrypnyk’s works, her contribution for development of this genre of lexicography.